POLA ASUH IBU BERHUBUNGAN DENGAN STATUS GIZI PADA BALITA : PARENTING PATTERNS RELATED TO NUTRITIONAL STATUS IN TODDLERS - Yunita Anita Lali Midu; Ronasari Mahaji Putri; Ragil Catur Adi Wibowo (Institut Kesehatan Hermina, 2021)
Many toddlers are still malnourished. Poor parenting style causes the growth and development of toddlers which is also not good. Poor nutritional status of children under five, lack of or obesity is associated with poor parenting. The purpose of this study was to identify the relationship between maternal parenting and the nutritional status of children under five in Tarung Village, Waikabubak City, West Sumba Regency. The research design used cross sectional. The population is mothers who have 34 children under five with a sample of 31 people taken by Simple Random Sampling Technique. The research instrument uses the Google Form application and KMS Book. The results of the study prove that almost half of mothers have poor parenting and most toddlers have poor nutritional status. The results of the statistical test obtained pvalue = (0.047) < (0.05) so that it was concluded that there was a relationship between maternal parenting and the nutritional status of children under five in Tarung Village, Waikabubak City, West Sumba Regency. For further researchers, it is recommended to consider the determinant factors of nutritional status that have not been studied.